Catalytic activity of C60 fullerene nanowhisker-silver nanoprism composite for reduction of 2-nitrophenol. Issue 5 (12th May 2022) - Ko, Jeong Won; Park, Se Hwan; Jeon, Sugyeong; Chung, Hoon; Ko, Weon Bae
Abstract: A silver nanoprism solution was prepared by reacting silver nitrate (AgNO3 ), trisodium citrate dihydrate (C6 H5 Na3 O7 ·2H2 O), sodium borohydride (NaBH4 ), and ascorbic acid (C6 H8 O6 ) in distilled water. The successful formation of the silver nanoprisms was confirmed by UV–visible spectroscopy considering the 350–400 nm and 600–650 nm wavelength ranges. The C60 fullerene nanowhisker- silver nanoprism composite was synthesized through a liquid-liquid interfacial precipitation (LLIP) method using C60 -saturated toluene, the silver nanoprism solution, and isopropyl alcohol and characterized by X-ray diffraction, Raman spectroscopy, scanning electron microscopy, and transmission electron microscopy. Its catalytic activity was assessed for the reduction of 2-nitrophenol by monitoring the reaction through UV–vis spectroscopy. A kinetics study was conducted, which indicated that the C60 fullerene nanowhisker-silver nanoprism composite catalyzed reduction of 2-nitrophenol follows a pseudo-first-order reaction.